A Review on Fiber Production Using Electrospinning Technique - Zakir Pardis, Mohammad; Polpalzai, Raihana (Journal of Natural Sciences – Kabul University, 2024)
Electrospinning is a wet-chemistry technology used for nanofabrication of functional coatings. With the emergence of nanotechnology, researchers have become more interested in studying the properties of nanoscale materials. Electrospinning, an electrostatic fiber fabrication technique, has recently displayed more interest and attention due to its versatility and potential for applications in diverse fields. The notable applications include tissue engineering, biosensors, filtration, and drug delivery inside the body. Over the years, more than 200 polymers have been electrocuted for various applications, and the number is increasing gradually. With these perspectives, this article aims to present an overview of the electrospinning technique and its promising advantages and potential applications. The article also discusses electrospinning theory, spinnable polymers, and parameters (solution and processing), which significantly affect fiber morphology, solvent properties, and melt electrospinning (alternative to electrospinning solution).